2022
DOI: 10.3389/fpsyg.2022.962492
|View full text |Cite
|
Sign up to set email alerts
|

The roles of motivation, anxiety and learning strategies in online Chinese learning among Thai learners of Chinese as a foreign language

Abstract: The impact of motivation, anxiety and learning strategies on the achievement of foreign language proficiency has been widely acknowledged in the context of traditional offline classroom settings. However, this issue has not been extensively documented in relation to online learning, which has become the predominant form of language learning during the period of the COVID-19 pandemic. The current study was conducted to investigate the relative prediction of motivation, anxiety and learning strategies for second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 151 publications
(259 reference statements)
0
15
0
Order By: Relevance
“…Similarly, statistical analysis in the U.S. context confirms the interplay between motivation and the learning environment during the learning process [21]. Additionally, CFL motivation was found to affect Thai learners' Chinese language proficiency while taking online Chinese courses [22].…”
Section: Motivation For Learning Chinese As a Foreign Languagementioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, statistical analysis in the U.S. context confirms the interplay between motivation and the learning environment during the learning process [21]. Additionally, CFL motivation was found to affect Thai learners' Chinese language proficiency while taking online Chinese courses [22].…”
Section: Motivation For Learning Chinese As a Foreign Languagementioning
confidence: 67%
“…It is clear from the literature that language learning motivation among CFL learners from diverse L1 backgrounds has not been studied extensively. Moreover, there have been relatively few studies on Chinese language learners outside mainland China [31], particularly in less developed countries [22]. The available literature shows that there is currently limited understanding of Turkish university students' L2 motivations for learning Mandarin Chinese.…”
Section: Rationale For the Current Studymentioning
confidence: 99%
“…Previous studies used different tests to measure L2 learners' proficiency (Hulstijn, 2012;McManus & Liu, 2020;Park et al, 2022;Tremblay, 2011;H. Zhang, 2018), and different measures could yield different research findings (W. Xu et al, 2022;H. Zhang, 2018H.…”
Section: External Aspects Of Construct Validitymentioning
confidence: 99%
“…In previous studies, scholars measured students' Chinese language proficiency through self-report and proficiency tests. The results showed that anxiety and motivation significantly predicted students' self-assessment results, and motivation affected students' self-assessment (Xu, Zhang, Sukjairungwattana, & Wang, 2022). Appropriately increasing task motivation can reduce anxiety and improve the efficiency of second language learning, but when students are determined to complete the task, the increase in task motivation is also accompanied by various factors that accelerate the increase in task anxiety (Wang, Zhu, & Zhang, n.d.).…”
Section: Research On the Influencing Factors Of Chinese Learning Moti...mentioning
confidence: 99%